YÜKSEKÖĞRETİM KURUMLARINDA GÖREV YAPAN PERSONELİN ÇEKİLMİŞ SAYILMASI - (:unkn) unknown (My University, 2013)
Çekilmiş sayılma, 657 sayılı Devlet Memurları Kanunu başta olmak üzere çeşitli kanunlarda ve Yükseköğretim Kurumları Yönetici, Öğretim Elemanı ve Memurları Disiplin Yönetmeliği nde düzenlenmiştir. Bununla birlikte, çekilmiş sayılmanın yükseköğretim kurumlarında çalışan personele uygulanırken esas alınacak hukuki metnin ne olduğu ve disiplin cezası olarak uygulanıp uygulanamayacağı ise tartışmalıdır. Bu tartışma suç ve cezalarda kanunilik ilkesinin disiplin hukukunda uygulanabilirliğiyle de yakından alakalıdır. Bu soruna ilişkin gerek yargı organları gerekse de doktrin tarafından savunulan farklı görüşler bulunmaktadır.

To be presumed have resigned is regulated in mainly the Civil Servants Law No. 657, different acts and the Disciplinary Regulations of Institutions of Higher Education Managers, University Lecturers and Officers . Together with, what the legal text which will be based on while to be presumed have resigned is being applied about the staff of higher education institutions is and whether to apply this act as a disciplinary punishment or not is controversial. This discussion is closely related to applicability of the legality principle of crime and punishments in disciplinary law. There are different opinions which are advocated by judicial branches and doctrine on this issue.
Being presumed to have resigned of staff in higher education institutions
Keywords: Eğitim, Eğitim Araştırmaları